The Effect of a Maternal Dairy-Free Lebanese Mediterranean Diet on Colic and Allergy Symptoms in Exclusively Breastfed Infants - Hanna, Marya (2020)
The origins of infantile colic are yet to be confirmed, however, multiple mechanisms have been proposed including cow’s milk protein allergy and presence of gut inflammation. The Mediterranean diet has numerous protective roles in multiple diseases, including its protective role observed in inflammatory and allergic diseases. In this study, we compared healthy exclusively breastfed infants whose mothers were either on their own typical diet (n=10) or on a dairy free Lebanese Mediterranean diet (LMD) (n=7). Mothers were recruited during pregnancy and assessed at weeks 2, 4 and 7 postpartum. Infant allergy and colic symptoms and behavior, including crying duration, were assessed using a questionnaire. Infant fecal sample were collected, and concentrations of eosinophil cationic protein (ECP) and pH were determined. Differences between the two groups were analyzed using the two sample independent t test and Mann-Whitney test depending on distribution of the variable while fisher’s exact test was used to evaluate the difference in categorical variables. Mothers in the intervention group scored higher on the dairy free LMD index (p=0.05). Daily consumption of dairy was lower for mothers on a dairy free LMD (p=0.01) while that of the remaining food groups was not statistically different. Infant fecal profile (ECP, p=0.971; pH, p=0.665), allergy and colic symptoms (p=0.447) were not statistically different between the two groups, but a trend towards lower crying duration in the second week was observed (p= 0.174). Although adherence to a dairy free LMD in exclusively breastfeeding mothers did not show substantial effects on infant allergy or colic symptoms, it is difficult to draw conclusions due to our small sample size. Further investigating the effects of maternal adherence to a LMD in exclusively breastfed infants is needed.